IMPLEMENTASI PEMBELAJARAN IPA BERDASARKAN KURIKULUM 2013 PADA KELAS V SDN 1 PENGAJARAN - Yusika Nabilla; Tri Jalmo; Rini Rita T. Marpaung (Universitas Lampung, 2015)
This research aimed to describe the implementation of curriculum 2013 on science learning in fifth grade in SDN 1 Pengajaran Bandar Lampung academic year 2014/2015 based on standard of process, scientific approach, and integrated thematic. Research samples were teachers who teach in fifth grade selected by purposive sampling. The type of data was qualitative data which is description of learning implementation in classroom by teacher. The results showed that the implementation of curriculum 2013 at the fifth grade learning activities have suitability to standard process with average score is 76.5% and categorized as